A GBT-based mixed finite element for curved thin-walled members with circular axis. (January 2020) - Peres, Nuno; Gonçalves, Rodrigo; Camotim, Dinar
Abstract: In this paper a mixed finite element based on Generalised Beam Theory (GBT) is proposed to analyse the first-order behaviour of naturally curved beams with circular axis (without pre-twist) and having deformable thin-walled cross-sections. The element applies the assumed strain concept to the longitudinal strains terms that are not present in straight members and cause locking. The additional strain DOFs are condensed out and therefore the stiffness matrix of the mixed element shares the DOFs of the standard (displacement-based) GBT finite element. The superior predictive capacity of the proposed mixed element with respect to the standard element with reduced integration is demonstrated through several examples involving complex global-distortional-local cross-section deformation. Highlights: An assumed strain GBT-based element is presented and validated. Arbitrary flat and thin-walled sections can be modelled. Curved members with circular axis can be handled. The proposed element is more efficient than the standard displacement-based GBT element.